Problematika Layanan Digital Perpustakaan Institut Agama Islam Negeri Curup dalam Meningkatkan Pemanfaatan Karya Ilmiah Institusi - Iswanto, Rahmat (IAIN Curup, 2019)
The article about the problems of the digital service of the library of IAIN Curup aims to find the real problems in developing this service. The difference between the concepts by the experts and the phenomena that occurred in the library of IAIN Curup led the author to carry out this research. The problem raised is how digital service in college libraries, how digital service in the library of IAIN Curup is and what problems are found in the field. This research method was carried out by analyzing the data qualitatively then giving an interpretation related to the existing concept. Data managed by the authors was one of the results of field observations and direct interviews with librarians related to the digital service of the library of IAIN Curup. The results found that many elements must be fulfilled by the library of IAIN Curup to build digital service. The identification of the problems in this study is the answer to the purpose of this study.